Spatio-Temporal Annual Changes of Mangrove Vegetation Coverages in Porong Estuary Based on Sentinel-2 Imagery - Herlambang Aulia Rachman; Abd Rahman As-Syakur (Universitas Trunojoyo Madura, 2023)
Mangrove is a typical coastal ecosystem with high productivity and has a number of ecosystem services. However this ecosystem is vulnerable particularly in urban areas due to land use change and illegal logging. Sidoarjo is one of the most developed urban area in the East Java Province, with mangrove ecpsystem scattered along the Porong estuary. This estuary is also the location of mudflow from the famous Lapindo mud disaster since 2006. This study aims to analyze the changes of mangrove coverages around the Porong estuary using satellite imagery data. Fractional Vegetation Coverage (Fv) was used to quantify the changes of mangrove vegetation coverage of Mangrove Forest from 2015 â€“ 2021. The results show that there is a change in mangrove coverages in the area of study. The high change from lo vegetation coverage (LVC) to Full Vegetation Covarege (FCV) as found in the mouth of Porong River. This condition maybe caused by sedimentation process due to mudflow from volcanic disasters.Â